Pemetaan Zona Penangkapan Nelayan Pancing Ulur (Hand Line) dan Keanekaragaman Jenis Ikan di Perairan Pesisir Kota Jayapura - Kalvin Paiki; Efray Wanimbo; Korinus Rejauw; Popi Ida Laila Ayer; Maklon Warpur (Cenderawasih University, 2023)
Small-scale fisheries are fishermen who catch fish to meet their daily needs and use fishing vessels of less than 5 gross tons (GT). Indonesia is a maritime country which is still dominated by actors in fisheries small scale, including in Jayapura City, with the main fishing gear being hand lines. Hand line fishing is one of the backbones of the people of Jayapura City with boats and fishing gear accounting for more than 50% of all fishing gear. This study aims to 1) Know the zoning of the fishing line operation area based on the waters of Jayapura City; 2) Knowing the composition of the catch (type and amount) and 3) knowing the abundance, diversity and uniformity of fish caught by hand line fishermen. This research was conducted in April-June 2023 in the waters of Jayapura City, data collection used the observation method; Interview and Documentation. Data analysis uses formulas, geostatistics, relative abundance, diversity and uniformity. The results of the study found that the distribution of fishing areas in Jayapura city waters was divided into three zones, namely the western zone from Tanjung Kayu Batu to Kampung Ormu, the eastern zone from Tanjung Skouw to Muara Tami and the middle zone from Tanjung Kayu Batu to Tanjung Skouw. In the western and eastern zones there are more fishing activities by local fishermen who use motor boats and katintin, while in the middle zone fishing activities are carried out by mixed fishermen, both using non-motorized boats (rowing boats) and motorized boats and katintin. Composition of fish species consisting of 21 species, total number of individuals 271, relative abundance ranged from 5.62% - 25.00, diversity ranged from 1.34-2.67, uniformity ranged from 0.74-0.91. Conclusion; the fishing zone consists of three zones namely west, east and central, the highest composition of fish species is found in natural fishing ground and the lowest is found in FADs, the highest abundance of fish is found in pelagic fish and the lowest is in demersal fish, diversity is classified as moderate and uniformity indicates no there is environmental disturbance to the distribution and abundance of fish in that location.